Pulsatile fatigue testing of arterial stents with radially applied load - Schmidt Wolfram; Brandt-Wunderlich Christoph; Kamke Frank; Schwerdt Christopher; Kaminsky Jörg; Behrens Peter; Schmitz Klaus-Peter; Grabow Niels (Current Directions in Biomedical Engineering)
Pulsatile fatigue testing is a basic requirement for arterial stents, however, there are several opportunities to setup and conduct the testing. The recently published standard guide ASTM F2477:2023 provides specific guidance, in particular includes the pressure controlled test method applying an outer hydraulic pressure to the test samples. The current work describes this approach, and demonstrates that the technical requirements can be met successfully. In addition, some inherent advantages are discussed, e.g. accuracy of pressure loading, absence of stent migration and potential high test frequencies.